PROJECT STRUCTURE DESIGN OF MUARA ANGKE FISH MARKET AS A TOURISM-BASED FISH MARKET - Owen Tanaka, Michael
Muara Angke Fish Market is a building that functions as a place to buy and sell fresh fish as well as a culinary tourism spot. This project is located in the Muara Angke area, North Jakarta. This project is located in a soft ground location and the earthquake acceleration is relatively high, so the building structure is designed as an earthquake-resistant building with seismic design category D. This project consists of 4 floors, semi-basement, ground floor, second floor, and mezzanine. This project is designed as a reinforced concrete structure in a functional building and a steel frame as the roof. The structure is modeled and analyzed using ETABS and SpColumn software and refers to SNI 2847:2019, SNI 1726:2019, SNI 1726:2020. Structural analysis was carried out by means of a two-stage analysis in which a seperation was made between the superstructure and the basement structure. The analysis of the upper structure was carried out using response spectral analysis and the analysis of the lower structure was carried out using equivalent lateral force analysis. The structural system used in the upper structure is the Special Moment Resisting Frame System (SMRFS) while the lower structure is a double system with Special Moment Resisting Frame System (SMRFS) and Special Structural Wall System (SSWS). The results of the analysis of the superstructure and basement are basic engineering design drawings on concrete structural elements such as beams, columns, slabs, and shear walls.